PENGARUH KONSENTRASI KARAGENAN TERHADAP SIFAT FISIK, KIMIA DAN ORGANOLEPTIK MINUMAN JELI NANAS (Ananas comosus L. Merr ) - Lina Widawati; Hendri Hardiyanto (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2016)
Pineapple preferred mainly related to flavor, taste and very interesting appearance. Jelly drink is a drink with high viscosity,with the addition of sugars, acids and water. This study aimed to determine the effect of carrageenan concentration on physical, chemical and organoleptic pineapple jelly drinks (Ananas comosus L. Merr). The research methods include crushing, screening, mixing, heating, removaling, and packaging. Treatment of each sample are the addition of carrageenan concentration at 0.15 %, 0.25 %, 0.35 %, 0.45 %, 0.55 %. The analysis in this study include vitamin C, viscosity and organoleptic (taste, color, and texture). The result of analysis vitamin C pineapple jelly drinks ranged from 1.13 mg/ g to 1.92 mg/ g. Analysis on the viscosity of the pineapple jelly drinks ranged between15.30 x 10-3 to 18.05 x 10-3. The average value of the color range between 3.1 (a bit like) to 3.65 (a bit like),average of flavor ranges between 3.2 (a bit like) to 3.6 (a bit like), and the average of texture ranged between 3.25 (a bit like) to 3.85 (somewhat like). Keywords : Carrageenan, jelly drinks, pineapple